2010
DOI: 10.1097/nmd.0b013e3181c8aa57
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Change in Levels of Depression and Personality

Abstract: This prospective longitudinal study investigated the role of the personality dimensions of dependency and self-criticism in the course of depressive symptoms in a sample of inpatient severely postpartum depressed mothers (n = 55). Depressive symptoms and personality were measured during hospitalization and on average 3 1/2 years later. In line with previous research, a considerable subgroup of mothers (39%) reported moderate to severe symptoms of depression at time 2. In addition, although these mothers did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Moreover, we did not study all personality traits; so future postpartum cohort studies should include other personality traits such as perfectionism (Mazzeo et al 2006; Gelabert et al 2011) and coping styles (de Tychey et al 2005). Recent preliminary data showed that self-criticism traits might also be an important factor in the persistence of depressive symptoms in postpartum depression (Vliegen et al 2010). However, we were interested in studied personality traits and other risk factors in the postpartum period.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we did not study all personality traits; so future postpartum cohort studies should include other personality traits such as perfectionism (Mazzeo et al 2006; Gelabert et al 2011) and coping styles (de Tychey et al 2005). Recent preliminary data showed that self-criticism traits might also be an important factor in the persistence of depressive symptoms in postpartum depression (Vliegen et al 2010). However, we were interested in studied personality traits and other risk factors in the postpartum period.…”
Section: Discussionmentioning
confidence: 99%
“…However the French version has more details on paternal disorders, drug treatments and past-history of both parents (Cazas et al 2004). In terms of drawing on the same empirical study, Vliegen and colleagues use the same sample and similar instruments (Vliegen et al, 2010;Vliegen et al 2013). …”
Section: Resultsmentioning
confidence: 99%
“…The remainder of the sources focused on multiple MBUs, with Howard et al (2004) focusing on 18 MBUs in the UK, Glangeaud-Freudenthal et al (2013) focusing on 13 in France and 3 in Belgium, GlangeaudFreudenthal et al (2011) andSutter-Dallay et al (2015) focusing on 13 in France, Elkin et al (2009) focusing on 12 in England, Glangeaud-Freudenthal and The MBU-SMF Working Group (2004) focusing on 11 in France and Belgium, Salmon et al (2003Salmon et al ( , 2004 and Abel et al (2005) focusing on eight MBUs and three facilities in the UK, Buist et al (2004) focusing on four in Australia, Vliegen et al (2010;2013) focusing on two in Belgium, and the remainder focusing on an unspecified multiple number in the UK (Howard, Shah, Salmon, and Appleby 2003) and Australia (Milgrom and Beatrice 2003).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations